Application of a memetic algorithm to the calibration of micro-lithography - Christoph, Dürr; Fühner, Tim; Tollkühn, Bernd; Erdmann, Andreas; Kókai, Gabriella (Hybrid Evolutionary Algorithms, 2007)
UnivIS-Import:2015-04-20:Pub.2007.tech.IMMD.IMMD2.applic

Efficient Analysis of Three Dimensional EUV Mask Induced Imageing Artifacts Using the Waveguide Decomposition Method - Shao, F.; Evanschitzky, Peter; Fühner, Tim; Erdmann, Andreas (BACUS, 2009)
UnivIS-Import:2017-07-10:Pub.2009.tech.IE.LEB.effici_83

Genetic Algorithms to Improve Mask and Illumination Geometries in Lithographic Imaging Systems - Fühner, Tim; Erdmann, Andreas; Farkas, Richard; Tollkühn, Bernd; Kókai, Gabriella (Applications of Evolutionary Computing - EvoWorkshops 2004: EvoBIO, EvoCOMNET, EvoHOT, EvoISAP, EvoMUSART, and EvoSTOC, 2004)
This paper proposes the use of a genetic algorithm to optimize mask and illumination geometries in optical projection lithography. A fitness function is introduced that evaluates the imaging quality of arbitrary line patterns in a specified focus range. As a second criterion the manufacturability and inspectability of the mask are taken into account. With this approach optimum imaging conditions can be identified without any additional a-priori knowledge of the lithographic process. Several examples demonstrate the successful application and further potentials of the proposed concept. © Springer-Verlag 2004.
UnivIS-Import:2015-04-16:Pub.2004.tech.IMMD.IMMD2.geneti_6

Incorporating Linkage Learning into the GeLog Framework - Fühner, Tim; Kókai, Gabriella (Proc. 3rd Conference of PhD Students in Computer Science, CS², 2002)
UnivIS-Import:2015-04-16:Pub.2002.tech.IMMD.IMMD2.incorp

Incorporating Linkage Learning into the GeLog Framework - Fühner, Tim; Kókai, Gabriella (Acta Cybernetica, 2003)
This article introduces modifications that have been applied to GeLog, a genetic logic programming framework, in order to improve its performance. The main emphasis of this work is the structure processing of genetic algorithms. As studies have shown, the linkage of genes plays an important role in the performance of genetic algorithms. Thus, different approaches that take linkage learning into account have been reviewed and the most promising has been implemented and tested with GeLog. It is demonstrated that the modified program solves problems that proved hard for the original system.
UnivIS-Import:2015-03-09:Pub.2003.tech.IMMD.IMMD2.incorp

Mask and Source Optimization for Lithographic Imaging Systems - Erdmann, Andreas; Farkas, Richard; Fühner, Tim; Tollkühn, Bernd; Kókai, Gabriella (Wave-Optical Systems Engineering II, SPIE 5182, 2003)
UnivIS-Import:2015-04-16:Pub.2003.tech.IMMD.IMMD2.maskan

Mask diffraction analysis and optimization for EUV masks - Erdmann, Andreas; Fühner, Tim; Evanschitzky, Peter (2010)
UnivIS-Import:2017-07-10:Pub.2010.tech.IE.LEB.maskdi

Optimization of one-and two dimensional masks in the optical lithography - Farkas, Richard; Kókai, Gabriella; Erdmann, Andreas; Fühner, Tim; Tollkühn, Bernd (Treffen der Fachgruppe Maschinelles Lernen, Wissensentdeckung, Data Mining der Gesellschaft für Informatik (FGML 2003), 2003)
UnivIS-Import:2015-04-16:Pub.2003.tech.IMMD.IMMD2.optimi

Rigorous diffraction simulations of topographic wafer stacks in double patterning - Shao, F.; Evanschitzky, Peter; Fühner, Tim; Erdmann, Andreas (Microelectronic Engineering, 2009)
Double patterning is regarded as a potential candidate to achieve the 32 nm node in semiconductor manufacturing. A key problem for a standard litho-etch-litho-etch (LELE) double patterning process is to evaluate and tackle the impact of the wafer topography resulting from the hardmask pattern on the second lithography step. In this paper, we apply rigorous electromagnetic field (EMF) solvers to investigate the wafer topography effects. At first, the studied 3D mask is split into two masks. The topography resulting from the exposure with the first split mask is described by a patterned hardmask. Based on that, the bottom antireflective coating (BARC) thickness of the second wafer stack is optimized. Alternatively, a two beam interference and the full diffraction spectrum of the second mask are used as the illumination of the wafer stacks, respectively. Finally, simulated 3D resist profiles for different BARC thicknesses are shown. The importance of wafer topography impact, the optimization of topographic wafer stacks, and the possible solutions to compensate for the impact of the wafer topography are discussed. © 2008 Elsevier B.V. All rights reserved.
UnivIS-Import:2017-07-10:Pub.2009.tech.IE.LEB.rigoro
Keywords: Double patterning; Dr.LiTHO; Lithography simulation; Topography effect; Wafer stack optimization; Waveguide method

Topography-aware BARC optimization for double patterning - Jahn, Johannes; Erdmann, Andreas; Fühner, Tim; Liu, S.; Shao, F.; Barenbaum, A. (Proceedings of the SPIE, 2010)
This paper aims at identifying appropriate bottom anti-reflective coatings (BARCs) for double patterning techniques such as Litho-Freeze-Litho-Etch (LFLE). A short introduction into the employed optimization methodology, including variables, figures of merit, models and optimization algorithms is given. A study on the impact of a refractive index modulation caused by the first lithographic step is presented. Several optimization surveys taking the index modulation into account are set forth, and the results are discussed. In addition to optimization procedures aiming at optimizing one litho step at a time, a co-optimization study for both litho steps is proposed. Finally, two multi-objective optimization procedures that allow for a post-optimization exploration and selection of optimum solutions are presented. Numerous solutions are discussed in terms of their anti-reflectance behavior and their manufacturing feasibility. © 2010 SPIE.
UnivIS-Import:2015-04-16:Pub.2010.nat.dma.pama21.topogr
Keywords: bottom anti-reflective coating (BARC); double patterning; lithography simulation; waferstack optimization

Will Darwins's Law Help Us to Improve Our Resist Models? - Tollkühn, Bernd; Fühner, Tim; Matiut, Daniela; Erdmann, Andreas; Semmler, Armin; Küchler, Bernd; Kókai, Gabriella (Advances in Resist Technology and Processing XX, 2003)
UnivIS-Import:2015-04-16:Pub.2003.tech.IMMD.IMMD2.willda